Ceci n’est pas le territoire: Transcending the Visual and Literary Frame - Dane Coult (Sillages Critiques)
This article explores the concept of frame theory and its relevance in understanding works of literature and art which feature devices traditionally associated with metafiction but which paradoxically avoid purely self-referential modes. By highlighting their aesthetic frames, these works invite audiences to engage in an artistic exchange that collapses the critical distance often associated with conceptual art in favor of a more immersive experience with the work, the artist, or the reality beyond the frame. A new term derived from ongoing research in frame theory, “frame transcendence,” provides a more satisfactory categorization of such works which historically have been incorporated into the realm of “meta-art”. By examining the work of David Foster Wallace and select works in the visual arts previously labeled as “metapainting,” the article seeks to demonstrate that this new categorization resolves critical problems that result when art simultaneously draws attention to its frame and to the authenticity of experience.